The Efficacy and Safety of Pirfenidone Combined With Immunosuppressant Therapy in Connective Tissue Disease-Associated Interstitial Lung Disease: A 24-Week Prospective Controlled Cohort Study - Wang, Jiaqi; Wang, Xiao; Qi, Xiaoyan; Sun, Zhijian; Zhang, Tao; Cui, Yi; Shu, Qiang (Frontiers in Medicine, 2022)
Objective: Interstitial lung disease (ILD) is a common manifestation of connective tissue disease (CTD) that manifests as several subtypes with significant differences in prognosis. It is necessary to evaluate the efficacy and safety of pirfenidone (PFD) combined with immunosuppressant (IS) in the treatment of CTD-ILD. Methods: A total of 111 CTD-ILD patients were enrolled, including those with systemic sclerosis (SSc), inflammatory myopathy (IIM), rheumatoid arthritis (RA) and other CTDs (such as systemic lupus erythematosus, primary Sjogren's syndrome and undifferentiated CTD). After evaluation of the high-resolution computed tomography (HRCT), pulmonary function (PF) and basic disease activity, patients either were or were not prescribed PFD and were followed up regularly for 24 weeks. Results: After 24 weeks of treatment, FVC% in the SSc-PFD group had improved by 6.60%, while this value was 0.55% in SSc-no-PFD patients. The elevation in FVC% was also significant in IIM-PFD over the IIM-no-PFD controls (7.50% vs. 1.00%). The DLCo% of RA-PFD was enhanced by 7.40%, while that of RA-no-PFD decreased by 5.50%. When performing a subtype analysis of HRCT images, the change in FVC% among SSc patients with a tendency towards usual interstitial pneumonia (UIP) was higher in those given PFD (SSc-PFD-UIP) than the no-PFD group (8.05% vs. -3.20%). However, in IIM patients with a non-UIP tendency, PFD displayed better therapeutic effects than the control (10.50% vs. 1.00%). DLCo% improved significantly in patients with the PFD-treated RA-non-UIP subtype compared with the no-PFD patients (10.40% vs. -4.45%). Dichotomizing the patients around a baseline FVC% or DLCo% value of 70%, the PFD arm had a more improved FVC% than the no-PFD arm within the high-baseline-FVC% subgroups of SSc and IIM patients (6.60% vs. 0.10%, 6.30% vs. 1.10%). In RA-PFD patients, DLCo% showed a significant increase in the subgroup with low baseline DLCo% compared to that in RA-no-PFD patients (7.40% vs. -6.60%). Conclusion: The response of PF to PFD varied between CTD-ILD subsets. SSc and IIM patients showed obvious improvements in FVC%, especially SSc-UIP and IIM-non-UIP patients. In RA, the subsets of patients with non-UIP and a lower baseline DLCo% most benefited from PFD.